Design of the integrated solid oxide fuel cell and molten carbonate fuel cell system to reduce carbon dioxide emissions - Jienkulsawad, Prathak; Saebea, Dang; Patcharavorachot, Yaneeporn; Arpornwichanop, Amornchai (My University, 2015)
In general, a solid oxide fuel cell (SOFC) based on an internal reforming operation cannot be run with complete fuel utilization; therefore, the remaining fuel needs to be effectively handled. Furthermore, the SOFC exhaust gas still contains carbon dioxide, which is the primary greenhouse gas, and searching for the way to utilize this carbon dioxide is important. A molten carbonate fuel cell (MCFC) appears to be a potential technology to mitigate the emissions of carbon dioxide. In this study, the performance of the integrated SOFC and MCFC system is analyzed. The SOFC is considered a main power generation and the MCFC is regarded as a carbon dioxide concentrator along with producing electricity as a by-product. Mathematical models of the SOFC and MCFC are based on one-dimensional mass balances taking into all various cell voltage losses under steady-state and isothermal conditions. Primary operating conditions of the integrated fuel cell system that affects the system efficiencies in terms of power generation and reduction in the carbon dioxide emission are discussed and its optimal operation is identified based on these criteria. Effect of carbon dioxide recirculation on the system is also studied. Various configurations of the integrated SOFC-MCFC system are proposed and compared to determine the suitable design of the integrated fuel cell system.